The effect of farming density on the growth of common carp Cyprinus carpio L.1758 raised in floating cages in the Thi-Qar province of the Euphrates River using Iranian feed - Dr. Kamil Kadhim Fahad; Mokhtar Jassim Nassir (University of Thi-Qar Journal of agricultural research, 2022)
From 18/10/2021 to 18/3/2022, samples were collected from private farms to cultivate fish in floating cages on the Euphrates River. Finally, different densities were studied to obtain the best farming density, in which three densities were used (63-43-23 fish/m3) by several 500 fish for the first process, 1000 fish for the second process, and 1500 fish for the third process, with a weighted rate of 100-120 gm, as a result, an originally Iranian feed was used for all three processes. The results of statistical analysis revealed that there are abstract differences (p0.05) in total weight gain, with the first process outperforming the rest of the process (130.0 gm/fish), followed by the second process (90.0 gm/fish). As well as the third process (75.0 gm/fish). Furthermore, the relative growth rate recorded when performing the statistical analysis that there are abstract differences (p0.05), in that the first process outperformed the second and third processes, with the first process outperforming the second (2.67 percent), the second (2.09 percent), and the third process outperforming the first (2.67 percent) (1.81 percent ). Because of the existence of abstract differences in the relative growth rate between the experiment months, the first process outperformed both the second and third processes. The first process has the highest relative growth rate (130.0 gm/fish), the second process has the highest relative growth rate (90.0 gm/fish), and the third process has the highest relative growth rate (75.0 gm/fish). Statistical analysis of the food conversion rate and food conversion efficiency revealed that there are abstract differences (p0.05) during the experiment months. So the food conversion rate recorded in the first process outperformed the second and third processes, and the highest food conversion rate was recorded for the first process (32.7 feed/gm), followed by the second process (22.5 feed/gm), and finally the third process (15.0 feed/gm). However, the food conversion efficiency demonstrated that the third process outperformed the first and second processes, while the second process outperformed the first. Furthermore, the food conversion efficiency values for the third process (12.5 percent), the second process (10.0 percent), and the first process (10.0 percent) are shown (7.22 percent ).